IMPLEMENTASI PERATURAN WALIKOTA SAMARINDA NOMOR 12 TAHUN 2016 TENTANG TUNJANGAN TAMBAHAN PENGHASILAN BAGI PEGAWAI NEGERI SIPIL DI BADAN KEPEGAWAIAN, PENDIDIKAN DAN PELATIHAN DAERAH KOTA SAMARINDA - Rosmini Rosmini; Adam Idris (Jurnal Administrative Reform, 2020)
This article will discuss and analyze the implementation of the Samarinda Mayor Regulation Number 12 of 2016 concerning Additional Income Allowances for Civil Servants at the Regional Personnel, Education and Training Agency of Samarinda City. By using a qualitative approach, data collection through observation, documentation, and interviews, as well as a descriptive analysis model with coding techniques, the results of the research shows that the implementation of the additional income allowance policy still experiences several obstacles that reduce the optimization of policy implementation, such as communication errors that still occur between implementers and employees, limited resources that affect the quality of performance, the process of disposition and division of tasks that are still not optimal, and SOPs that have not been optimally implemented are related to too large a workload, so that the role and function of monitoring cannot be carried out.Keywords: implementation, allowances, additional income